Low-Temperature Hydrothermal Treatment (Htt) Improves the Combustion Properties of Short-Rotation Coppice Willow Wood by Reducing Emission Precursors - Diaz-Robles, L (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The worldwide transformation from fossil fuels to sustainable energy sources will increase the demand for biomass. However, the ash content of many available biomass sources exceeds the limits of national standards. In this study, short-rotation coppice willow biomass was hydrothermally treated at 150, 170 and 185◦C. The higher heating value increased by 2.6% from x = 19,279 J × g−1 to x = 19,793 J × g−1 at 185◦C treatment temperature. The mean ash content was reduced by 53% from x = 1.97% to x = 0.93% at 170◦C treatment temperature, which was below the limit for category TW1b of the European pellet standard for thermally treated biomass. The nitrogen, sulfur and cadmium concentrations were reduced below the limits for category TW1b of the European biomass pellet standard (N: from 0.52% to 0.34%, limit at 0.5%; S: from 0.051% to 0.024%, limit at 0.04%; Cd: from 0.83 mg × kg−1 to 0.37 mg × kg−1, limit at 0.5 mg × kg−1 ). The highest reduction rates were sampled for phosphor (80–84%), potassium (78–90%), chlorine (96–98%) and lithium (96–98%). The reduction behavior of the elements is discussed according to the chemical processes at the onset of hydrothermal carbonization. The results of this study show that HTT has the potential to expand the availability of biomass for the increasing worldwide demand in the future. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.